Synthesis of Copper Oxide Aided by Selective Corrosion in Cu Foils - Roberto Baca Arroyo (Advances in Materials Science and Engineering)
Copper oxide films aided by selective corrosion have been synthesized. Using copper (Cu) foils of commercial printed circuit boards (PCBs), chemical attack in small areas on Cu surfaces and their oxidation with heating process in air atmosphere at low temperature have allowed to produce Cu oxide layers. Phase formation of Cu oxide samples was validated by X-ray diffraction studies, and their conduction properties were registered and evaluated by current-voltage curves. Stability analysis of the Cu oxide samples was conducted by a correlation profile between average strain and Cu oxide percentage grown, which confirms that the structure defects dependent on plastic deformation define the existence of both CuO and Cu2O phases beneficial to mitigate corrosion and advance in Cu oxide-based devices to build electronic circuits as components on PCBs.